واقع بيئة العمل الإبداعية في أكاديميات الإعلام الرقمي وفق أفضل الممارسات العالمية لإدارة المواهب: The Reality of the Creative Work Environment In Digital Media Academies According to the Best International Practices For Talent Management - Isa bin Fadhil bin Saif al-Hosni; Abdul Kadir, Fakhrul Adabi (Journal Al-Muqaddimah, 2024)
This study aimed to identify the reality of the creative work environment represented by (organizational structure, training, technology, incentives, and working conditions) on talent management represented by (planning the workforce of talented people, motivating and developing talented workers, and evaluating the performance of talented workers) in academies. Digital media. The researcher followed the descriptive analysis method. The study derives its importance from researching the relationship of the creative work environment to talent management. The research was chosen due to the lack of organizations’ focus on knowing the importance of the creative work environment that may affect talent management and reflect on their creativity. Therefore, the problem of the study lies in answering the main question: What is the reality of the creative work environment in digital media academies according to the best international practices for talent management? The study was conducted on a random sample, and the study population consisted of all employees of digital media academies, who numbered (250) employees. The sample was selected and distributed electronically according to the sample size determination table developed by Cressy and Morgan, which consisted of (175) employees. The researcher designed a questionnaire to measure the study variables. The study concluded with a set of results, the most prominent of which is that there is a statistically significant effect at the significance level (0.05) of the creative work environment represented by (organizational structure, training, technology, incentives, working conditions) on talent management represented by (planning for a talented workforce, motivating... And developing talented workers, evaluating the performance of talented workers) in digital media academies. The study recommended many recommendations, the most prominent of which were: working to improve the work environment for employees in digital media academies, especially with regard to the organizational structure, training,... incentives, Do not overlook this as it is positively linked to talent management.